Mysterious Looks of Typhoid Fever: A New Experience - Basak, Deepankar Kumar; Gomes, Richmond Ronald; Ahmed, Md Ashraf Uddin; Alam, ABM Sarwar E (Bangladesh Critical Care Journal, 2015)
Enteric fever (typhoid or paratyphoid) is a common infectious disease worldwide, especially in developing countries like Bangladesh. Typhoid fever caused by the gram negative bacterium Salmonella typhi that may have a wide spectrum of clinical presentations. We report a case of a 17 year old previously healthy college boy who presented with fever, abdominal pain and shortness of breath later on who was eventually diagnosed as having typhoid fever complicated by acute pancreatitis, hepatitis and severe pulmonary hypertension. Enteric fever presenting as acute pancreatitis and pulmonary hypertension is a rare entity and must be considered in endemic areas like Bangladesh, in patients presenting with fever and concomitant severe abdominal pain and shortness of breath, as any delay in timely institution of treatment can prove fatal. There are very few case reports in the world which have depicted this unusual association. Bangladesh Crit Care J March 2015; 3 (1): 36-38